Escenarios relativos al establecimiento de agenda para la gobernanza transgeneracional de los recursos y servicios hídricos. (2016)
Based on a review of economic, political, environmental, health, social and psychological scenarios, a documentary study was conducted with a selection of sources indexed in Latin American repositories −Dialnet, Latindex and Redalyc−, considering the period from 1987 to 2016 and with the purpose of specifying ten models for the study of the governance of water resources and services. In relation to other reviews, the specified models are contrasted and it is recommended to include variables related to the agenda establishment, a key factor to explain the influence of public policies on the behavior of users of the potable water service.